Urticaria and Angioedema - Zuberbier, Torsten; Grattan, Clive; Maurer, Marcus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Urticaria and Angioedema provides a practical, comprehensive review of all types and aspects of urticaria and angioedema important to the clinician. Its content is completely up-to-date—taking into consideration both current guidelines and all recent literature—and highlights current knowledge about pathophysiology focuses on the clinically relevant aspects of diagnosis and treatment includes a full range of standard operating procedures features patient information leaflets in a copy-ready format offers indispensable assistance in the daily practical management of urticaria patients This clinical guide is an invaluable resource for all physicians specializing in dermatology, allergy, internal medicine, pediatrics and general medicine. USPs: This guide offers invaluable assistance in the daily practical management of urticaria patients. It highlights the current knowledge about pathophysiology, and focuses on the clinically relevant aspects of diagnosis and treatment. It includes a full range of standard operating procedures, as well as patient information leaflets in a copy-ready format. Written by internationally renowned experts.
History of Urticaria -- Aetiopathogenesis of Urticaria -- Classification of Urticaria -- Impact of Urticaria: QOL and Performance -- Acute Urticaria -- Chronic Urticaria -- Dermographic and Delayed Pressure Urticaria -- Heat and Cold Urticaria -- Solar Urticaria -- Cholinergic Urticaria and Exercise-Induced Anaphylaxis -- Contact Urticaria -- Urticarial Syndromes and Autoinflammation -- Urticaria Vasculitis -- Angioedema -- Therapy of Urticaria -- Standard Operating Procedures: A Practical Approach.
Keywords: Dermatology; Allergy; Pediatrics; Dermatology; Allergology; Pediatrics